PENGARUH SISTEM PEMBAYARAN, CASH ON DELIVERY (COD) DAN KEPUASAN KONSUMENTERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE - Kurnia, Tria Esti; Ratnawili, Ratnawili (UM. Bengkulu, 2024)
This study aims to determine the effect of the Cash On Delivery (Cod) Payment System and Consumer Satisfaction on Purchase Decisions at E-Commerce Shopee. This type of research is quantitative research with a descriptive approach. The population of this study were Umb Management Study Program Students Class of 2019. The number of research samples was 64 people. Data collection was carried out using a questionnaire. The data analysis technique uses multiple linear regression analysis techniques. The results of the analysis show that partially the Cash On Delivery (Cod) Payment System has a positive and significant effect on purchasing decisions (tcount = 6.406 and Sig = 0.004), and Consumer Satisfaction has a positive and significant effect on purchasing decisions (tcount = 4.568 and Sig = 0.0023) . Simultaneously there is the influence of the Cash On Delivery (Cod) Payment System and Consumer Satisfaction on Purchase Decisions at E-Commerce Shopee (Fcount = 25,802 and Sig = 0,000). Keywords: Payment System, COD, Consumer Satisfaction, Purchase Decisions